Coexistência de predadores em paisagens agrícolas: a diferenciação do nicho alimentar representa um mecanismo importante? - Almeida, Ana Beatriz De [UNIFESP] (2020)
Coexisting species that occupy the same ecological niche potentially compete, and for long-term coexistence theory predicts a differentiation in at least one of the three main axes of the ecological niche: a) time, b) space or c) resources. In this study, we investigated wether differentiation in the use of food resources among species represent an important mechanism for the coexistence of four coexisting predators (Maned wolf - C. brachyurus, Crab-eatingfox - C. thous, Hoary fox - L. vetulus and Cougar - P. concolor) in an agricultural landscape. We expected in general a low overlap in food resources among species, and especially that a) the diet of P. concolor differs from the other species mostly by the more frequent consumption of medium-sized to large mammals and b) high differentiation between C. thous and L. vetulus due to their taxonomic and corporal similarity increasing competition. We analyzed 207 fecal samples collected during three years in a private farm with Eucalyptus matrix between remnants of Atlantic Forest and Cerrado, identifying food items to the lowest possible taxonomic level. We calculated frequency- and percentage of occurrence, niche breadth and niche overlap between all four species. Contrary to the expectations, we found extreme overlap of food resources among almost all species pairs, and there also was no increased consumption of medium-sized to large mammals by P. concolor, which refutes our hypothesis. There are two possible explanations for these results: 1) there's no competition between the predators due to high availability of prey, making mechanisms to enable coexistence unnecessary or 2) competition among species is reduced by differing in another axis of ecological niche (i.e. space and/or time). Given the knowledge of the probability of high abundance of some resources (e.g. generalist small mammals) in modified landscapes like the study area, the absence of competition for food resources mediated by a high availability of these resources seems more probable. The results indicate thateven highly modified agricultural landscapes represent viable habitats for the four predators species with similar food demands, calling attention to their potential value conservation efforts and restauration of habitat.